Immobilization of α-amylase on gold nanorods: An ideal system for starch processing. Issue 9 (September 2015) - Homaei, Ahmad; Saberi, Dariush
Graphical abstract: Highlights: Gold nanorods have been considered suitable for immobilization of α-amylase. Immobilization α-amylase on gold nanorods enhances enzyme stability and efficiency. The temperature profile of immobilized α-amylase showed a broad range of activity compared with free form. Immobilization α-amylase on gold nanorods, opening new opportunities for food industry applications. Abstract: Immobilization of α-amylase was carried out by ionic exchange and hydrophobic interactions on gold nanorods (GNRs) synthesized via sequential seed mediated growth method. The optimum temperature of α-amylase increased from 50 to 60 °C and its optimum pH was shifted from 6 to 7 upon immobilization. The kinetic parameters, K m and V max values were 3 mg/ml and 6.4 μm min −1 for free and 3.4 mg/ml and 5.91 μm min −1 for immobilized enzymes, respectively. The immobilization process brought significant enhancement of stability to temperature and extreme pH values with respect to free α-amylase. Enzyme shows higher functionality than the free form when incubated for long time (1 h) at 80 °C and at extreme pH values (3 and 10). In addition to improving thermal stability, the storage stability of α-amylse exhibited a significant increase upon immobilization which makes it a biocatalyst of possible industrial application, specially a potential candidate for production of glucose syrups on industrial scale.